Manajemen Konflik dalam Organisasi: Tinjauan Literatur Sistematis tentang Variasi Jenis, Faktor Penyebab, dan Strategi Penanganan (Jurnal Manajemen Kreatif dan Inovasi, 2025)
Conflict is an inevitable phenomenon in every organization, whether in business, education, or social contexts. If not managed properly, conflict has the potential to reduce performance; however, if handled constructively, it can become a source of innovation. Based on this issue, this study aims to answer the main question: how is conflict understood and managed according to recent literature findings? The method used is a literature review by searching for articles through several online databases using the keywords "organizational conflict," "conflict management," "types of conflict," and "resolution strategies." From an initial search result of 17 articles, after a screening process, 15 articles met the criteria for further analysis. The analysis results reveal three main themes. First, conflict in organizations can be categorized into several types, such as intrapersonal, interpersonal, intragroup, and intergroup conflicts. Second, the sources of conflict often stem from differences in interests, ineffective communication, and unequal distribution of resources. Third, conflict resolution strategies vary, including mediation, collaborative communication, compromise, deliberation, and approaches based on religious values.